Nilai Moralitas dalam Pembentukan Peraturan Perundang-Undangan - Suryani Suryani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
The legislators should make the value of Pancasila a fundamental value or as the source of all sources of law, bringing consequences for the legislators to become a guide and guide in carrying out legislative functions. Ironically, the reality is that the legislators show that there are paradigmatic problems and a crisis of ethical awareness in the formation and enforcement of laws in Indonesia. What emerges is law development and law enforcement that is stagnant, centralized, corrupt and very far from divine and humanist values, and far from achieving social justice. The actualization of Divine Values as the fundamental value of Pancasila should be accommodated and become the basis for legislators in carrying out their functions and duties in the formation of laws or laws and transformed into laws that they form, so that they will give birth to laws that are effective and have divine dimensions. humanity, unity and social justice.Keywords: Morality; Legislation; Regulation.